Incorporating the gender dimension on the use of rice technologies in Latin America - González, C.; Twyman, Jennifer; Labarta, Ricardo Antonio; Muriel, J; García, M. (2014)
A presentation on the role of men and women in rice in Peru, Bolivia and Ecuador. In collaboration with the CGIAR Research Program on Rice.